Laminate Ply Stacking Sequence Optimization with Fibers Orientation Imperfections - Latalski, J. (Engineering Transactions, 2004)
The paper discusses the fiber orientations imperfections effect on the optimum design of a laminate plate exposed to compressive load. It is assumed that fibers angular imperfection for each design variable cannot exceed maximum allowable deviation from variable’s nominal value. These maximal accepted deviations are called tolerances. The incorporation of tolerances into the design algorithm is achieved by diminishing the limiting values of state variables by the product of assumed tolerances and appropriate sensitivities. Therefore, the given method allows to introduce tolerances into the design in a relatively simple way and ensures safe results. The paper is illustrated by examples of the rectangular laminate plate minimum thickness design. Numerical results show the reliability-based design to be important for structural safety compared to the approach where tolerances are not taken into account.